2018
DOI: 10.1590/1980-57642018dn12-010002
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and depression in older adults with and without cognitive impairment

Abstract: Low physical activity and depression may be related to cognitive impairment in the elderly.Objetive:To determine depression and physical activity (PA) among older adults with and without cognitive impairment.Methods:156 older adults, both males and females, aged ≥60 years, were asked to complete the Thai Mini-Mental State Examination (Thai-MMSE), a global cognitive impairment screening tool. Seventy-eight older adults with cognitive impairment and 78 older adults without cognitive impairment were then separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
(35 reference statements)
3
12
0
3
Order By: Relevance
“…Advanced age (i.e., mean ≥ 70 years; odds ratio (OR): 4.67; 95% confidence interval (CI): 2.42–8.24), high TGDS scores (OR: 2.34; 95% CI: 1.22–4.45), MCI (OR: 0.23, 95% CI: 0.05–0.96), and low physical activity levels (OR: 2.51; 95% CI: 1.34–4.56) were significant risk factors for sarcopenia in older adults in the unadjusted analysis. It has been previously reported that differences in age, sex, and educational levels might partially explain low physical activity, depression, and cognitive impairment [ 2 ]. Therefore, we conducted a multivariate analysis adjusted for potential confounding variables (i.e., age, sex, and educational levels) and found independent associations with sarcopenia risk for physical activity, depression, and MCI (ORs = 1.96, 2.09, and 0.22, respectively; p s < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced age (i.e., mean ≥ 70 years; odds ratio (OR): 4.67; 95% confidence interval (CI): 2.42–8.24), high TGDS scores (OR: 2.34; 95% CI: 1.22–4.45), MCI (OR: 0.23, 95% CI: 0.05–0.96), and low physical activity levels (OR: 2.51; 95% CI: 1.34–4.56) were significant risk factors for sarcopenia in older adults in the unadjusted analysis. It has been previously reported that differences in age, sex, and educational levels might partially explain low physical activity, depression, and cognitive impairment [ 2 ]. Therefore, we conducted a multivariate analysis adjusted for potential confounding variables (i.e., age, sex, and educational levels) and found independent associations with sarcopenia risk for physical activity, depression, and MCI (ORs = 1.96, 2.09, and 0.22, respectively; p s < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Further, a systematic review and meta-analysis comprising 15 observational studies indicated that patients with sarcopenia were likely to have depression [ 10 ]. Further, Yuenyongchaiwat et al [ 2 ] reported that older adults with cognitive impairment had lower physical activity levels and higher depression levels, compared to individuals without cognitive impairment. Therefore, depression is associated with poor cognitive performance, which often relates to insufficient physical activity or lack of exercise, which could be a contributing factor to sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study highlighted a significant difference in the proportion of women with low MMSE scores compared to men. Besides the impact of gender, this difference could also be attributed among other potential factors to the lower levels of education and the higher prevalence of depression amongst participating women (33,34). However, more evidence is needed for safe explanations.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Many studies have been done to identify appropriate forms of exercise and training that prevent the decline of cognitive function (Lista and Sorrentino, 2010) and reduce the risk of depression (Yuenyongchaiwat et al, 2018) during aging. In response to physical activity, there is an increase in BDNF levels in the brain and peripheral blood (Kang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%